2012
DOI: 10.1111/j.1600-0684.2012.00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of specific‐pathogen‐free (SPF) rhesus macaques to better model oral pediatric cytomegalovirus infection

Abstract: Congenital human cytomegalovirus (HCMV) infection can result in lifelong neurological deficits. Seronegative pregnant woman often acquire primary HCMV from clinically asymptomatic, but HCMV-shedding children. Potential age-related differences in viral and immune parameters of primary RhCMV infection were examined in an oral rhesus CMV infection model in specific pathogen free macaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Yet, congenital virus transmission can be modeled using both guinea pigs and nonhuman primate models [7,24]. In particular, rhesus macaques and their corresponding endogenous rhesus CMV (RhCMV) are a highlyrelevant model for understanding adult/fetal HCMV pathogenesis [25,26] and congenital infection [9,27], as the physiology/immunology of rhesus monkey pregnancy is highly analogous to humans [25], there is extensive protein homology between RhCMV and HCMV [28], and certain mechanisms of viral immune evasion are conserved between these viruses [29,30]. Previously, our group demonstrated that the depletion of CD4 + T cells followed by intravenous RhCMV inoculation of seronegative pregnant monkeys resulted in consistent RhCMV congenital infection and a high rate of fetal loss [24].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, congenital virus transmission can be modeled using both guinea pigs and nonhuman primate models [7,24]. In particular, rhesus macaques and their corresponding endogenous rhesus CMV (RhCMV) are a highlyrelevant model for understanding adult/fetal HCMV pathogenesis [25,26] and congenital infection [9,27], as the physiology/immunology of rhesus monkey pregnancy is highly analogous to humans [25], there is extensive protein homology between RhCMV and HCMV [28], and certain mechanisms of viral immune evasion are conserved between these viruses [29,30]. Previously, our group demonstrated that the depletion of CD4 + T cells followed by intravenous RhCMV inoculation of seronegative pregnant monkeys resulted in consistent RhCMV congenital infection and a high rate of fetal loss [24].…”
Section: Introductionmentioning
confidence: 99%
“…While HCMV host entry is hard to track, the ubiquity of mammalian CMV implies that their parasitism long preceded human emergence and that animal and human CMVs should behave similarly. Orally inoculated rhesus CMV can infect macaques ( 6 ). However, experimental inoculation involves giving high virus doses to sedated animals, making respiratory contamination hard to exclude, and again, no oral infection site has been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, direct inoculation of RhCMV in naïve rhesus monkeys via subcutaneous or IV routes causes quantifiable, persistent infection, which allows assessment of the efficacy of prophylactic strategies. Oral RhCMV challenge and natural vertical transmission models via co-housing with RhCMV-seronegative monkeys are also being trialed as more physiologically-relevant challenge models that can better recapitulate human CMV transmission [39]. …”
Section: Rhcmv Acquisition and Persistencementioning
confidence: 99%